Effect of helical rolling on the bainitic microstructure and impact toughness of the low-carbon microalloyed steel; Materials Science and Engineering: A; Vol. 816 - Derevyagina L. S. Lyudmila Sergeevna; Gordienko A. I. Antonina Ildarovna; Surikova N. S. Natalya; Volochaev M. N. Mikhail (2021, 2021)
Title screen